ASUHAN KEPERAWATAN DENGAN PENATALAKSANAAN TEKNIK RELAKSASI GENGGAM JARI DAN NAFAS DALAM TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Rifka Zalila; Dewi Sartika (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2021)
Background : Hypertension is a medical condition characterized by increased contraction of arteries which causes resistance to blood flow which increases blood pressure against the walls of blood through narrow blood vessels. Objective : To determine the effect of finger grip relaxation techniques and deep breathing on reducing blood pressure in hypertensive patients. Methods : Research design with descriptive method with case study approach. The implementation of Hypertension nursing care was carried out in the internal medicine room starting from June 15 to June 21, 2021. The subjects in this study were 2 patients suffering from hypertension morning and afternoon. Results : After being treated for 3 days, the results showed that the blood pressure of both patients decreased in patient 1 Mr “I” from 180/100 mmHg to 160/90 mmHg, in patients 2 Mrs “S” from 160/100 mmHg to 140/90 mmHg the pain scale of the two patients from 6 (moderate) to 3 (mild) the body is not weak, has started to be energetic and can sleep at night. cooperation between the health team and patients and families is very necessary for the success of nursing care for patients. Conclusion : With the management of finger grip relaxation techniques and deep breathing to reduce blood pressure in hypertensive patients with the results of the nursing evaluation the problem was partially resolved.